Lost in citations: Why standard metrics fail archaeology and regional scholarship. A critical analysis of bibliographic indexing and research evaluation. - Di Renzoni, Andrea (Ex Novo: Journal of Archaeology, 2025)
This article explores the development, structure, and implications of bibliographic indexes and research metrics in contemporary academic publishing. It traces the historical evolution of indexing services from early systems like Index Medicus to modern platforms such as Web of Science, Scopus, Google Scholar, Dimensions, and OpenAlex. The study highlights how varying inclusion criteria, ranking algorithms, and citation policies among databases produce significantly different representations of scholarly output. It critically examines key metrics (e.g., Impact Factor, h-index, CiteScore, SNIP, SJR), assessing their impact on journals, authors, and institutions. It shows how current evaluation systems, including issues of classification and disciplinary bias, does not reflect the quality and impact of research outputs in the Humanities and Social Sciences, and especially in Archaeology. This is particularly evident in Italian prehistoric archaeology, explored here as a case study. The paper also addresses the ethical dilemmas linked to peer review, predatory publishing, and metric manipulation, advocating for more transparent, pluralistic, and context-sensitive approaches to scientific assessment. The final section reflects on the peculiarities of archaeological data and publication practices, underlining the inadequacy of conventional metrics for evaluating scientific contribution in this field.